2017
DOI: 10.1016/j.micres.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial magnetosome and its potential application

Abstract: Bacterial magnetosome, synthetized by magnetosome-producing microorganisms including magnetotactic bacteria (MTB) and some non-magnetotactic bacteria (Non-MTB), is a new type of material comprising magnetic nanocrystals surrounded by a phospholipid bilayer. Because of the special properties such as single magnetic domain, excellent biocompatibility and surface modification, bacterial magnetosome has become an increasingly attractive for researchers in biology, medicine, paleomagnetism, geology and environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 140 publications
0
62
0
2
Order By: Relevance
“…Once absorbed, these ions can be readily removed by magnetic separation. [ 270 ] For example, an MTB strain UPB‐MAG05 has been found to be highly tolerant of Cd ions and can absorb these ions from Cd‐polluted waters. [ 271 ]…”
Section: Applicationsmentioning
confidence: 99%
“…Once absorbed, these ions can be readily removed by magnetic separation. [ 270 ] For example, an MTB strain UPB‐MAG05 has been found to be highly tolerant of Cd ions and can absorb these ions from Cd‐polluted waters. [ 271 ]…”
Section: Applicationsmentioning
confidence: 99%
“…The biological production of the biomineralized magnetosomes is strictly controlled at the gene level, and the magnetosomes are normally formed in different sizes and shapes in magnetosome membrane [6] . Magnetosome synthesis has recently been proposed as a model for the formation of prokaryotic organelles and biomineralization [8,9] . Although the details of the mechanism for the synthesis of magnetosomes are not exactly clear, studies have shown that the formation of magnets is a cellular process that depends on several stages, including the separation of the internal membrane of the cell, the transfer of ions, the crystallization of magnetite within these vesicles, and the formation and arrangement of adult crystals as a linear structure of the cellular skeleton [1,10] .…”
Section: Introuductionmentioning
confidence: 99%
“…When the ultrastructural details of BMs were first reported in 1980, it generated much interest . The distinctive characteristics of BMs suggested that they could be used as an effective vehicle, particularly as a potential magnetic carrier for drugs.…”
Section: Discussionmentioning
confidence: 99%